2014
DOI: 10.1039/c4cc04580g
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous vanadium oxide coating on graphene by atomic layer deposition for stable high energy lithium ion anodes

Abstract: Uniform amorphous vanadium oxide films were coated on graphene via atomic layer deposition and the nano-composite displays an exceptional capacity of ~900 mA h g(-1) at 200 mAg(-1) with an excellent capacity retention at 1 A g(-1) after 200 cycles. The capacity contribution (1161 mA h g(-1)) from vanadium oxide only almost reaches its theoretical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 15 publications
1
39
0
Order By: Relevance
“…A large number of new graphene-containing hybrids was also tested for the fi rst time (see Table 2 ) as LIB anode active materials (e.g., graphene-containing cobaltites, [291][292][293] carbonates, [ 294,295 ] sulfi des, [ 296,297 ] nitrides, [298][299][300][301] [ 309 ] Sb, [ 310 ] Sn-In, [ 311 ] In 2 O 3 , [ 312 ] Co 2 (OH) 3 Cl, [ 313 ] LiVPO 4 F, [ 314 ] V 2 O 3 [ 315 ] and V 2 O 5 [ 316 ] hybrids) but, unfortunately, none could entirely fulfi l the requirements of the ideal anode material for LIBs, although two hybrids [ 291,303 ] displayed a promisingly low 1 st cycle irreversible capacity (i.e., <20%).…”
mentioning
confidence: 99%
“…A large number of new graphene-containing hybrids was also tested for the fi rst time (see Table 2 ) as LIB anode active materials (e.g., graphene-containing cobaltites, [291][292][293] carbonates, [ 294,295 ] sulfi des, [ 296,297 ] nitrides, [298][299][300][301] [ 309 ] Sb, [ 310 ] Sn-In, [ 311 ] In 2 O 3 , [ 312 ] Co 2 (OH) 3 Cl, [ 313 ] LiVPO 4 F, [ 314 ] V 2 O 3 [ 315 ] and V 2 O 5 [ 316 ] hybrids) but, unfortunately, none could entirely fulfi l the requirements of the ideal anode material for LIBs, although two hybrids [ 291,303 ] displayed a promisingly low 1 st cycle irreversible capacity (i.e., <20%).…”
mentioning
confidence: 99%
“…[9,46] As exemplified in some reports, some amorphous aerogels or xerogel prepared are featured with low density, highly porous and high surface area and are being explored as new promising materials in electrochemistry. [47][48][49][50][51] Gao et al demonstrated amorphous V 2 O 5 exhibited superior Na storage performance compared with its crystalline counterpart.…”
Section: Amorphous V 2 Omentioning
confidence: 99%
“…V 2 O 5 is intensively studied materials both as cathode and anode for LIBs because of a high specific capacity, natural abundance, and relatively low cost 17 18 . If consider a fully reduction from V 5+ to V 0 , V 2 O 5 gains a theoretical capacity of 1472 mAhg −1 , the highest capacity among all metal oxides, and thus can be an ideal component for high energy anodes 19 20 21 22 . Despite this unique property, there is limited data on the high potential capacity of the V 2 O 5 anodes that enables a stable cyclic performance 22 23 24 .…”
mentioning
confidence: 99%
“…Researchers have proposed ways to overcome this, for instance, Sun et al . coated graphene on amorphous V 2 O 5 via an atomic layer deposition method to enhance its electronic conductivity and electrochemical activity 19 .…”
mentioning
confidence: 99%